2017
DOI: 10.1002/ajmg.a.38241
|View full text |Cite
|
Sign up to set email alerts
|

Variable developmental delays and characteristic facial features—A novel 7p22.3p22.2 microdeletion syndrome?

Abstract: Isolated 7p22.3p22.2 deletions are rarely described with only two reports in the literature. Most other reported cases either involve a much larger region of the 7p arm or have an additional copy number variation. Here, we report five patients with overlapping microdeletions at 7p22.3p22.2. The patients presented with variable developmental delays, exhibiting relative weaknesses in expressive language skills and relative strengths in gross, and fine motor skills. The most consistent facial features seen in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…LFNG, like PDGFalpha, seems a priori well tolerated (pLI = 0.42). This was in agreement with the study of Yu et al (7). There, they discussed the implication of this gene in the phenotype of their patients, and concluded that haploinsufficiency of only LFNG could not be the cause of the phenotype of these 5 patients.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…LFNG, like PDGFalpha, seems a priori well tolerated (pLI = 0.42). This was in agreement with the study of Yu et al (7). There, they discussed the implication of this gene in the phenotype of their patients, and concluded that haploinsufficiency of only LFNG could not be the cause of the phenotype of these 5 patients.…”
Section: Discussionsupporting
confidence: 94%
“…The deleted 7p22 region spans 58 genes, including some that could be linked with the clinical signs of patient 1. There is also a large sequence overlap with patients 4 and 5 of Yu and colleagues' case report (7), which is similarly dysmorphic, with no reported hematologic manifestations. In this study, the patients displayed weaknesses in language skills, as well as in motor skills.…”
Section: Introductionmentioning
confidence: 59%
“…Mundy described decreased myelination in such cases [17]. Yu described unspecific hypomyelination in a 3-year-old child [38]. Ommeron described delayed myelination at a few weeks of age [19].…”
Section: Discussionmentioning
confidence: 99%
“…Andrea C. Yu reported 5 patients with microdeletions at 7p22.3p22.2. [ 44 ] The most facial features in these patients include a broad nasal root, a prominent forehead a prominent glabella and arched eyebrows, micrognathia, metopic ridging or craniosynostosis, cleft palate, cardiac defects, and mild hypotonia. Micrognathia is also present, but no gene is found to be associated with this phenotype in this region.…”
Section: Discussionmentioning
confidence: 99%